Direct to operating room trauma resuscitation decreases mortality among severely injured children. Issue 4 (October 2018) - Wieck, Minna M.; Cunningham, Aaron J.; Behrens, Brandon; Ohm, Erika T.; Maxwell, Bryan G.; Hamilton, Nicholas A.; Adams, M. Christopher; Cole, Frederick J.; Jafri, Mubeen A.
Abstract : BACKGROUND: Expediting evaluation and intervention for severely injured patients has remained a mainstay of advanced trauma care. One technique, direct to operating room (DOR) resuscitation, for selective adult patients has demonstrated decreased mortality. We sought to investigate the application of this protocol in children. METHODS: All DOR pediatric patients from 2009 to 2016 at a pediatric Level I trauma center were identified. Direct to OR criteria included penetrating injury, chest injuries, amputations, significant blood loss, cardiopulmonary resuscitation, and surgeon discretion. Demographics, injury patterns, interventions, and outcomes were analyzed. Observed mortality was compared with expected mortality, calculated using Trauma Injury Severity Score methodology, with two-tailed t tests, and a p value less than 0.5 was considered significant. RESULTS: Of 2, 956 total pediatric trauma activations, 82 (2.8%) patients (age range, 1 month to 17 years) received DOR resuscitation during the study period. The most common indications for DOR were penetrating injuries (62%) and chest injuries (32%). Forty-four percent had Injury Severity Score (ISS) greater than 15, 33% had Glasgow Coma Scale (GCS) score of 8 or less, and 9% were hypotensive. The most commonly injured body regions were external (66%), head (34%), chest (30%), and abdomen (27%). Sixty-seven (82%) patients required emergent procedural intervention, most commonly wound exploration/repair (35%), central venous access (22%), tube thoracostomy (19%), and laparotomy (18%). Predictors of intervention were ISS greater than 15 (odds ratio, 14; p = 0.013) and GCS < 9 (odds ratio = 8.5, p = 0.044). The survival rate to discharge for DOR patients was 84% compared with an expected survival of 79% (Trauma Injury Severity Score) ( p = 0.4). The greatest improvement relative to expected mortality was seen in the subgroup with penetrating trauma (84.5% vs 74.4%; p = 0.002). CONCLUSION: A selective policy of resuscitating the most severely injured children in the OR can decrease mortality. Patients suffering penetrating trauma with the highest ISS, and diminished GCS scores have the greatest benefit. Trauma centers with appropriate resources should evaluate implementing similar policies. LEVEL OF EVIDENCE: Diagnostic tests or criteria, level II.